Is It Really Gender? An Empirical Investigation Into Gender Effects in Technology Adoption Through the Examination of Individual Differences - Aguirre-Urreta, Miguel; Marakas, George (Human Technology, 2010)
A recent development in the technology acceptance literature is the inclusion of gender as a moderator of the relationships between intention and its antecedents, such that some are stronger for men than women, and vice versa. While the effects have been well established, the mechanisms by which they operate, that is, which specific gender differences are in operation and how they affect intention to adopt, have not been thoroughly explored. In this research, psychological constructs with established gender differences, such as core self-evaluations, computer self-efficacy and anxiety, psychological gender-role, and risk-taking propensity, are examined. In addition, this research introduces a novel context for the study of technology adoption in that more than a single alternative is offered to participants, thus requiring a choice among technologies. Results indicate that gender effects are more complex than previously thought, with potentially multiple influences from different facets operating simultaneously.